Prevalensi Kelainan Kongenital Janin pada Kehamilan Penderita HIV/AIDS di RSUD Dr. Soetomo Kota Surabaya - Rista Elva Riani; Arief Bakhtiar; Dewi Setyowati; Manggala Pasca Wardhana; Tri Pudy Asmarawati (Universitas Malahayati Lampung, 2024)
ABSTRACT HIV infection in pregnancy is at risk of causing various complications in the mother and fetus, one of which is congenital abnormalities. This study aims to determine the prevalence of congenital abnormalities in pregnancy of women with HIV / AIDS. Retrospective descriptive study with cross-sectional design using medical record data of HIV-positive pregnant women at Dr. Soetomo Surabaya Hospital for the 2020-2022 period. There were 108 pregnant women with HIV, 3 of whom (2.8%) had congenital abnormalities in the fetus in the form of hydrocephalus, Dandy-Walker syndrome, and CPAM. Suspected to be associated with opportunistic infections and embryo-toxic effects of the ARV drug efavirenz. In pregnant women with HIV at Dr. Soetomo General Hospital, 3 (2.8%) pregnant women experience congenital abnormalities in the fetus, for that it is necessary to prevent and early detection of complications during pregnancy, as well as the selection of ARV regimens that are safer for fetal development. Keywords: Pregnancy With HIV/AIDS, HIV/AIDS, Congenital Abnormalities ABSTRAK Infeksi HIV pada kehamilan berisiko menyebabkan berbagai komplikasi pada ibu dan janin, salah satunya kelainan bawaan. Penelitian ini bertujuan untuk mengetahui prevalensi kelainan bawaan pada kehamilan ibu dengan HIV/AIDS. Studi deskriptif retrospektif dengan desain cross-sectional menggunakan data rekam medis ibu hamil HIV-positif di RSUD Dr. Soetomo Surabaya periode 2020-2022. Ada 108 wanita hamil dengan HIV, 3 di antaranya (2,8%) memiliki kelainan bawaan pada janin berupa hidrosefalus, sindrom Dandy-Walker, dan CPAM. Diduga terkait dengan infeksi oportunistik dan efek toksik embrio dari obat ARV efavirenz. Pada ibu hamil dengan HIV di Rumah Sakit Umum Dr. Soetomo, 3 (2,8%) ibu hamil mengalami kelainan bawaan pada janin, untuk itu perlu dilakukan pencegahan dan deteksi dini komplikasi selama kehamilan, serta pemilihan regimen ARV yang lebih aman bagi perkembangan janin. Kata Kunci: Kehamilan Dengan HIV/AIDS, HIV/AIDS, Kelainan Bawaan